The Analysis of The Influence of Information about The Covid-19 Pandemic on Toddlers’ Parenting - Emy Sutiyarsih; Narita Diatanti; Eli Lea WP (Journal of Ners and Midwifery, 2022)
The government's policy in implementing the New Normal to prevent the spread of COVID-19 has changed all aspects of society, including the family environment. In current conditions, parenting is the most important thing in determining optimal child development (Dewi and Khotimah, 2020). The conditions of parenting and communication in the family have both positive and negative impacts on children's development.  (Kuswanti, Munadhil, Zainal & Oktarina, 2020). The aim of this study was to analyze the effect of information about the COVID-19 pandemic on toddlers’ parenting. This study was a cross-sectional analytical study. This study used a bivariate data analysis with Chi Square test. The findings showed that the p-value was (0.0001) < 0.05, so it could be concluded that there was a significant influence between the received information and toddlers’ parenting. Therefore, it is necessary to have the right information about the COVID-19 pandemic so that mothers can make the right and correct choices about parenting for toddlers.